Tuning Electronic Transport Properties of Zigzag Graphene Nanoribbons with Stone-Wales Defect - Nguyen, Tien Thanh; Bui, Hoc Thai; Nguyen, Ut Van; Le, Tuan (Communications in Physics, 2018)
Influences of the symmetric Stone-Wales (SW) defect on the electronic transport properties of the zigzag graphene nanoribbons (ZGNRs) has been studied using ab initio simulation based on density functional theory (DFT) combined with non-equilibrium Green’s function (NEGF) technique. The calculated transmission spectra T(E) at various bias windows, device densities of states (DDOS), current characteristics as well as local density of states (LDOS) of the defective asymmetric and symmetric ZGNRs are presented in comparison of those for the pristine ZGNRs. It has been established the metallic character of the electronic transport in asymmetric ZGNRs, and in symmetric ones, the current has a semiconductor behavior, with negative differential resistance (NDR) effect. Symmetric SW defect, as a most unfavorable SW defect type for electric conductance, remarkably decreases the current values, but does not change the character of conductivity in both the asymmetric and symmetric ZGNRs. NDR has been explained by the altering by SW defect the number of frontier molecular orbitals entering bias windows